PERAN PEDAGANG PEREMPUAN LANJUT USIA DALAM MENINGKATKAN EKONOMI KELUARGA - Meiliniawati, Ni Kadek Ardani Putri (Journal of Development Economic and Social Studies, 2022)
The demographic bonus period currently entered by Indonesia will be great opportunity should the country is able to take advantage from the abundance of productive population. However, the period also leads to the aging population trend, where the number of older population is high. In Tabanan regency, the involvement of elderly females in public sector increases every year. One of the driver for them to remain active at work is culture. The purpose of this study is to analyze the role of elderly female sellers in Tabanan traditional market in increasing the economy of their family. This qualitative research uses the ethnographic approach related with the perspective of culture. The data was acquired through unstructured interviews and direct observations. This research finds that elderly female sellers in Tabanan traditional market plays an instrumental role in maintaining and increasing their family’s economy. Even though they are involved in public sector activities, they do not leave their obligations in domestic sector and duties as Hindus. This research implies the necessity of old age insurance in informal sector, inclusive formal education improvement in all remote areas, and non-profit organizations engaged in woman empowerment in order to create awareness about the importance of gender equality.